Promotion Approach for The Elderly Health Tourism In Nakorn-nayok Province - Suansri, Matura; Suansri , Somkid; Jungprawat, Patcharin (Community and Social Development Journal, 2022)
The objectives of this study were: 1) to examine potential of stakeholders on management of health tourism, and 2) to investigate an approach to promote the elderly health tourism in Nakorn-Nayok Province. The mix methods of quantitative and qualitative research were conducted.. The samples were 24 samples, namely, community leaders, representatives of subdistrict administrative organization, and local entrepreneurs, who were selected by a purposive sampling. The instrument was an interviews using semi-structured questionnaires. analyze the SWOT and TOWS Matrix to establish proactive strategy to enhance the potential of health tourism. The statistics used in the study were frequency, percentage, mean and standard deviation. The results showed that the potential of health tourism promotion for the elderly, as a whole, was at a high level. From the in-depth interview, it was found that stakeholders needed development of health tourist attractions for the elderly in their own areas. They thought that in Nakorn-Nayok, its nature and attractions were distinctive and appropriate for health tourism and also had health personnel and experts. There was a concrete learning center with good health instructors for the elderly, which was a good point in the community. The weak points were that the health tourism management was not good enough and lack of knowledge transfer because new generation took on other jobs resulting in no continuous knowledge management and new technology changed the way of life in community. Therefore, the community leaders proposed an approach to promote the elderly health tourism as follows: an appropriate community management with strong leaders and a serious cooperation from people in community. An appropriate, well-planned tourism activities should meet the needs of the elderly and a health tourism for the elderly should be promoted continuously.